2002
DOI: 10.1002/ett.4460130603
|View full text |Cite
|
Sign up to set email alerts
|

Delay analysis of a probabilistic priority discipline

Abstract: Abstract. In computer networks, the Strict Priority (SP) discipline is perhaps the most common and simplest method to schedule packets from different classes of applications, each with diverse performance requirements. With this discipline, however, packets at higher priority levels can starve packets at lower priority levels. To resolve this starvation problem, we propose to assign a parameter to each priority queue in the SP discipline. The assigned parameter determines the probability or extent by which its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…This paper extends the average delay analysis of the PP scheduling discipline in [10] to the multi-class case, derives several useful relationships concerning the average queueing delays of different classes and verifies the analytical results through simulation and implementation on a real DiffServ testbed. The implementation on the DiffServ testbed provides a proof of concept of the applicability of the PP discipline in real networks.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…This paper extends the average delay analysis of the PP scheduling discipline in [10] to the multi-class case, derives several useful relationships concerning the average queueing delays of different classes and verifies the analytical results through simulation and implementation on a real DiffServ testbed. The implementation on the DiffServ testbed provides a proof of concept of the applicability of the PP discipline in real networks.…”
Section: Introductionmentioning
confidence: 79%
“…An in-depth analysis of the delay performance of the twoclass PP system is given in [10]. A decomposition approach was proposed for calculating the average queueing delay and upper and lower bounds were obtained.…”
Section: Formal and Experimental Results For Pp Scheduling Disciplinementioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [5,6,9] showed that this algorithm exhibits the following properties that are very desirable to achieve service differentiation in a multi-class network by (a) providing diverse delay differentiation between classes, (b) supporting for weighted max-min fairness among classes, (c) overcoming the starvation problem inherent in SP, (d) supporting relative differentiated services, and (e) providing explicit bandwidth reservation guarantees by appropriate setting of a parameter…”
Section: Related Workmentioning
confidence: 99%